2022
DOI: 10.1021/acs.est.2c04390
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Assimilatory Nitrate Reduction as a Previously Overlooked Pathway of Reactive Nitrogen Transformation in Estuarine Suspended Particulate Matter

Abstract: Suspended particulate matter (SPM) contributes to the loss of reactive nitrogen (Nr) in estuarine ecosystems. Although denitrification and anaerobic ammonium oxidation in SPM compensate for the current imbalance of global nitrogen (N) inputs and sinks, it is largely unclear whether other pathways for Nr transformation exist in SPM. Here, we combined stable isotope measurements with metagenomics and metatranscriptomics to verify the occurrence of dissimilatory nitrate reduction to ammonium (DNRA) in the SPM of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Screening and identification of novel enzymes are performed by function-based or sequence-based. Hu et al proved that suspended particulate-matter that are present in nitrate-contaminated estuarine river contained genes of dissimilatory nitrate reductase ( nirBD ) using metagenomics libraries [ 96 ]. They were able to prove that diverse alpha-and gamma-proteobacteria that are present in the suspended particulate matters played a crucial role in the conversion of nitrate to ammonia and therefore regarded as key active heterotrophic bacteria.…”
Section: Strategies For Improving the Catalytic Properties Of Enzymes...mentioning
confidence: 99%
See 1 more Smart Citation
“…Screening and identification of novel enzymes are performed by function-based or sequence-based. Hu et al proved that suspended particulate-matter that are present in nitrate-contaminated estuarine river contained genes of dissimilatory nitrate reductase ( nirBD ) using metagenomics libraries [ 96 ]. They were able to prove that diverse alpha-and gamma-proteobacteria that are present in the suspended particulate matters played a crucial role in the conversion of nitrate to ammonia and therefore regarded as key active heterotrophic bacteria.…”
Section: Strategies For Improving the Catalytic Properties Of Enzymes...mentioning
confidence: 99%
“…They were able to prove that diverse alpha-and gamma-proteobacteria that are present in the suspended particulate matters played a crucial role in the conversion of nitrate to ammonia and therefore regarded as key active heterotrophic bacteria. This conversion helps to balance the ecosystem in the nitrate-contaminated estuarine river [ 96 ]. Finally, metagenomics libraries could also assist to screen newly synthesized Escherichia coli that are assembled from different DNA gene circuits which are comprised of transporters, promoters with terminators.…”
Section: Strategies For Improving the Catalytic Properties Of Enzymes...mentioning
confidence: 99%
“…In a previous study, it was found that nirBDencoded nitrite reductase can not only catalyze fermentation-modedependent DNRA but also regulate ANR (Luque-Almagro et al, 2011). Nitrite reductase (NirBD) and assimilatory nitrate reductase (NasA) can work together to enable ANR to proceed properly (Hu et al, 2022). In the microbial nitrogen cycle, ANR is a form of anabolic metabolism in which nitrate is first reduced to nitrite by NasA, then nitrite is converted to ammonia (Reitzer, 2003).…”
Section: Nitrogen Metabolismmentioning
confidence: 99%
“…The reactive nitrogen transformation pathway via ANR sometimes occurs at more than the DNRA and denitrification (Hu et al, 2022).…”
Section: Nitrogen Metabolismmentioning
confidence: 99%
“…[25][26][27][28] Gastrointestinal microorganisms reduce nitrate to nitrite, and oxidize ferrous ions in hemoglobin to ferric ions, thus rendering the oxygen transport mechanism of red blood cells ineffective. [29][30][31][32] Impaired oxygen transport can lead to cyanosis, fatigue, shortness of breath, cerebral hypoxia, and even death. [33][34][35][36][37] Therefore, it is necessary to develop some efficient methods to treat nitrate to reduce the impact on human beings.…”
Section: Introductionmentioning
confidence: 99%